Answer:90
Step-by-step explanation:To solve this expression, we need to follow the order of operations (PEMDAS):
1. Start by simplifying inside the parentheses:
35 - 7 + 5 * (-12) - (42 + 65 - 351) ÷ 2
= 35 - 7 + 5 * (-12) - (107 - 351) ÷ 2
= 35 - 7 + 5 * (-12) - (-244) ÷ 2
= 35 - 7 + 5 * (-12) + 122
2. Next, perform the multiplication and division:
35 - 7 + 5 * (-12) + 122
= 35 - 7 - 60 + 122
= 28 - 60 + 122
= -32 + 122
= 90
Therefore, the result of the expression 35−7+5×(−12)−(42+65−351) ÷ 2 is 90.